2018
DOI: 10.3389/fpls.2018.00417
|View full text |Cite
|
Sign up to set email alerts
|

Newly Identified Wild Rice Accessions Conferring High Salt Tolerance Might Use a Tissue Tolerance Mechanism in Leaf

Abstract: Cultivated rice (Oryza sativa L.) is very sensitive to salt stress. So far a few rice landraces have been identified as a source of salt tolerance and utilized in rice improvement. These tolerant lines primarily use Na+ exclusion mechanism in root which removes Na+ from the xylem stream by membrane Na+ and K+ transporters, and resulted in low Na+ accumulation in shoot. Identification of a new donor source conferring high salt tolerance is imperative. Wild relatives of rice having wide genetic diversity are reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 68 publications
1
56
0
Order By: Relevance
“…Even though Typha species are invasive, dominating over native aquatic species under moderate salinity, they can germinate only after being returned to non-saline conditions [39], and the most salt-tolerant species (Typha domingensis) can only tolerate salinities up to 15 ppt [40,41]. In addition, rice, which according to the KIs and historical maps, was also cultivated in the area prior to 1960, is a salt-sensitive crop that becomes unproductive when soil salinity reaches 7 ppt [42].…”
Section: Discussionmentioning
confidence: 99%
“…Even though Typha species are invasive, dominating over native aquatic species under moderate salinity, they can germinate only after being returned to non-saline conditions [39], and the most salt-tolerant species (Typha domingensis) can only tolerate salinities up to 15 ppt [40,41]. In addition, rice, which according to the KIs and historical maps, was also cultivated in the area prior to 1960, is a salt-sensitive crop that becomes unproductive when soil salinity reaches 7 ppt [42].…”
Section: Discussionmentioning
confidence: 99%
“…The chlorophyll content, ChlF imaging, and tissue ion contents (Na + and K + ) were estimated as described above, on a daily basis, from both freshwater-and saline water-dipped sample. From the collected data, daily chlorophyll degradation rate and tissue tolerance (LC 50 score represents a sodium concentration where half (50%) of the chlorophyll pigments were destroyed) was calculated for each genotype (Prusty et al, 2018).…”
Section: Tissue-tolerance Assay-leaf Clip Methodsmentioning
confidence: 99%
“…This can also be achieved by maintaining the cellular ionic homeostasis by effective K + retention (Munns and Tester, 2008). Previous studies reported genetic variations in rice for salt-tolerance strategies (Roy et al, 2014;Prusty et al, 2018;Chakraborty et al, 2019). The mechanism of ion exclusion is strongly associated with the expression of SOS pathway genes, where salt stress induces calcium signal by activating SOS2/SOS3 complex, which further activates SOS1, a plasma membrane Na + /H + antiporter (Martinez-Atienza et al, 2007;Munns and Tester, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several breeding programmes have used O. sativa cultivars, such as Pokkali and Nona Bokra, as salt‐tolerant parent donors, incorporating Saltol and other salt tolerance genes . However, the allelic variation required to breed stress‐tolerant crops must now be expanded by introgressing genes from wild relatives because of the relatively small proportion of the total genetic diversity in the genus Oryza found in O. sativa . Salinity tolerance of other key crop species, such as durum wheat ( Triticum durum ) and tomato ( Solanum lycopersicum ), has been improved using natural allelic variation.…”
Section: Introductionmentioning
confidence: 99%
“…Endemic Australian rice species have been identified as a source of tolerance to abiotic and biotic stress in cultivated rice . Tissue tolerance to Na + in seven pantropical wild rice species was reported recently, implying the presence of key tolerance genes in the Oryza CC and DD genomes . Membrane transporters are a vital part of the control of influx, efflux, and partitioning of Na + and Cl − .…”
Section: Introductionmentioning
confidence: 99%